2013
DOI: 10.1371/journal.pone.0085073
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid and Cannabinoid-Like Fatty Acid Amide Levels Correlate with Pain-Related Symptoms in Patients with IBS-D and IBS-C: A Pilot Study

Abstract: AimsIrritable bowel syndrome (IBS) is a functional gastrointestinal (GI) disorder, associated with alterations of bowel function, abdominal pain and other symptoms related to the GI tract. Recently the endogenous cannabinoid system (ECS) was shown to be involved in the physiological and pathophysiological control of the GI function. The aim of this pilot study was to investigate whether IBS defining symptoms correlate with changes in endocannabinoids or cannabinoid like fatty acid levels in IBS patients.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 38 publications
2
37
1
Order By: Relevance
“…Although endocannabinoid levels were not examined in serum and synovial fluid from non-OA patients, serum endocannabinoid levels in our study are similar to previous reports of healthy and non-OA patients and did not correlate with pain, suggesting that the serum endocannabinoid tone is not altered by OA [11,16,18,19]. Our negative results in regard to endocannabinoids and chronic OA pain are in agreement with a recent clinical report demonstrating that inhibition of the endocannabinoid hydrolyzing enzyme fatty acid amide hydrolase, and consequent elevation of PEA, OEA, and AEA levels, does not alter pain in OA patients [22].…”
Section: Discussionsupporting
confidence: 86%
“…Although endocannabinoid levels were not examined in serum and synovial fluid from non-OA patients, serum endocannabinoid levels in our study are similar to previous reports of healthy and non-OA patients and did not correlate with pain, suggesting that the serum endocannabinoid tone is not altered by OA [11,16,18,19]. Our negative results in regard to endocannabinoids and chronic OA pain are in agreement with a recent clinical report demonstrating that inhibition of the endocannabinoid hydrolyzing enzyme fatty acid amide hydrolase, and consequent elevation of PEA, OEA, and AEA levels, does not alter pain in OA patients [22].…”
Section: Discussionsupporting
confidence: 86%
“…These results rule against a possible anti-prokinetic effect of endogenous PEA following the experimental post-inflammatory functional increase in intestinal motility. Recently, increased PEA levels in the plasma (Fichna et al, 2013) and in the colon (Zhang et al, 2014) of IBS patients have been reported.…”
Section: Discussionmentioning
confidence: 98%
“…Variants of the CNR1 and FAAH genes have been observed in patients with diarrhea-predominant and alternating forms of IBS 82-84 . Levels of FAAH mRNA are reduced in intestinal tissues of patients with constipation-predominant IBS 85 . These genetic polymorphisms and alterations in gene expression are associated with alterations in GI motility and sensation, supporting the pathophysiologic significance of alterations in the ECS in the gut.…”
Section: Cannabinoids and Control Of Gi Motilitymentioning
confidence: 96%